2014
DOI: 10.3844/ajabssp.2014.466.473
|View full text |Cite
|
Sign up to set email alerts
|

Self-Incompatibility and Effect of Reciprocal Cross and Open Pollination on Fruit Set and Fruit Characteristic in Jordanian Almond Landraces

Abstract: Limited studies were carried out to identify self-and cross-compatibility relationships among Jordanian almond landraces. Therefore, this study aimed at studying the level of self-incompatibility and the effect of cross and open pollination on fruit set and shell, nut and kernel related traits in almond. To achieve this objective, field experiments were carried out during 2012 and 2013 cropping season on five Jordanian almond landraces and one wild bitter almond (A. communis) available in the farmer's fields a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In addition, it has been stated that the nut shape may deteriorate in case of an increase in the number of nuts in cluster, which is a type of hazelnut and can change depending on climatic conditions and maintenance conditions (Balık et al 2014). Owais (2014) reported that pollinators cause a significant change in kernel shape in almonds. On the other hand, it has been noted that selfpollination in almonds causes irregular fruit shape (Graselly and Olivier, 1988;Torre Grossa et al, 1994) and abortive kernel (Torre Grossa et al, 1994).…”
Section: Figure 3 Plant and Catkins Image Of Pollinator Genotypesmentioning
confidence: 99%
“…In addition, it has been stated that the nut shape may deteriorate in case of an increase in the number of nuts in cluster, which is a type of hazelnut and can change depending on climatic conditions and maintenance conditions (Balık et al 2014). Owais (2014) reported that pollinators cause a significant change in kernel shape in almonds. On the other hand, it has been noted that selfpollination in almonds causes irregular fruit shape (Graselly and Olivier, 1988;Torre Grossa et al, 1994) and abortive kernel (Torre Grossa et al, 1994).…”
Section: Figure 3 Plant and Catkins Image Of Pollinator Genotypesmentioning
confidence: 99%
“…Ak (2001) indicated that nut weight, nut width and shell thickness of pistachio generally varied with the pollinators. Owais (2014) indicated that pollen source resulted in slight changes in shell, nut and kernel characteristics of almonds. Golzari et al (2016) reported significant effects of pollinator types on kernel diameter, kernel weight, shell thickness, oil and protein ratio of walnuts.…”
Section: Shell Thicknessmentioning
confidence: 99%
“…Çetiner et al (1984) indicated that pointy nut shape of Sivri and İncekara cultivars with the greatest transformation ratio of florets into husk distorted homogeneity and product quality in hazelnut orchards. Owais (2014) indicated that pollinator types resulted in significant changes in shell shape of almonds. .00 e 1.20 ab The differences among the treatments indicated with the same letter vertically were not significant at P<0.05.…”
Section: Nut Shape Indexmentioning
confidence: 99%